2015
DOI: 10.1038/jcbfm.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Fibrinolysis with Tissue Plasminogen Activator is Associated with Transient Cerebrospinal Fluid Inflammation: A Randomized Controlled Trial

Abstract: Locally administered tissue plasminogen activator (TPA) accelerates clearance of intraventricular hemorrhage (IVH), but its impact on neurologic outcomes remains unclear and preclinical research suggests it may have pro-inflammatory effects. We randomly allocated patients with ruptured cerebral aneurysms and IVH, treated with endovascular coiling and ventricular drainage, to receive either 2-mg intraventricular TPA or placebo every 12 hours. Cerebrospinal fluid (CSF) and serum cytokine and white blood cell (WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
(67 reference statements)
5
21
0
Order By: Relevance
“…A more recent trial found that intraventricular tPA had no effect on the need for CSF shunt dependency or the functional outcome of adults with endovascular-treated aneurysmal SAH [ 147 ]. Recent data suggest that the sudden release of blood breakdown products by fibrinolysis might fail to protect against hydrocephalus because inflammation is increased by rapid blood clot lysis [ 148 ]. Nevertheless, there remains the possibility that tPA in children with posthemorrhagic hydrocephalus might offer some long-term benefits unrelated to the development of ventriculomegaly.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent trial found that intraventricular tPA had no effect on the need for CSF shunt dependency or the functional outcome of adults with endovascular-treated aneurysmal SAH [ 147 ]. Recent data suggest that the sudden release of blood breakdown products by fibrinolysis might fail to protect against hydrocephalus because inflammation is increased by rapid blood clot lysis [ 148 ]. Nevertheless, there remains the possibility that tPA in children with posthemorrhagic hydrocephalus might offer some long-term benefits unrelated to the development of ventriculomegaly.…”
Section: Resultsmentioning
confidence: 99%
“…Kramer et al 29 reported that IVF with rt-PA in patients with ruptured brain aneurysms and IVH produces a transient local inflammatory response, the severity of which is associated with the degree of fibrinolysis, suggesting it may be induced by release of hemoglobin degradation products, rather than rt-PA itself. This suggests that accelerated removal of IVH by IVF might decrease the incidence of ventriculitis by decreasing the accumulation of blood degradation products in the cerebrospinal fluid, and raises an intriguing question as to whether intraventricular co-administration of drugs which activate Heme Oxygenase-1 (which catalyzes the degradation of heme), such as deferoxamine mesylate could enhance the efficacy of IVF in IVH 3032 .…”
Section: Discussionmentioning
confidence: 99%
“…Alteplase administration induces a transient local inflammatory response by promoting the release of hematoma breakdown products after ICH. 90 All drainage fluid samples were collected before the use of alteplase in this study. We did not investigate whether alteplase enhanced the local inflammatory response after MIS.…”
Section: F I G U R E 4 Influence Of Time From Symptom Onset To Mis Lmentioning
confidence: 99%